DECISION-MAKING IN SOLVING MATH PROBLEMS ON ELEMENTARY SCHOOL STUDENTS - VINA AMILIA SUGANDA M (Sriwijaya University Learning and Education International Conference, 2016)
Mathematics is one of the subjects given to the basic and high education level with a view to achieving the national education goals. Learning mathematics are given to students not only focused to develop cognitive and psychomotor aspect, but there are also aspects of affective in it. As for the affective aspects of learning mathematics that is reflected, namely to train the student's independence stance and attitude to appreciate the usefulness of mathematics. Learning math is perceived by some students is the abstract subjects, whereas mathematics is related to daily activities. This impact to students being not serious in answering and resolving a given math teacher. Not looking back the question after answering became one of the reasons students are wrong in making decisions when completing a math problem. Level of the primary school became the primary focus in the writing of this article.